POJAVNOST STRANSKIH UČINKOV PRI OBSEVANJU RAKA DANKE IN ANALNEGA KANALA Z UPORABO BOLUSA...Radiological Societies Engineers of Slovenia Proceedings and lectures posters IV. Congress, 25-26 May, 2018, Zreče, Slovenia. - Anej, Razboršek; Karmen, Štrljič; Ester, Verstovšek; Valerija, Žager Marciuš (Bulletin: Newsletter of the Society of Radiographers of Slovenia & the Chamber of Radiographers of Slovenia)
Introduction and purpose: Rectal and anal canal cancers are among the leading causes of death nowadays. One of the treatment methods is also radiotherapy. On account of surface tumors and due to the characteristics of the photonic beam at depth, a bolus is used in order to enable the dose to increase toward the surface; however, this also increases the prominence of side effects on the skin and mucous membrane. The purpose of the research is to determine which side effects are caused by the use of a bolus in irradiation of the above-mentioned cancers, how they present themselves, and when they appear. Methods: The descriptive method with a systematic literature review was used. The data were obtained retrospectively by means of the Webdoctor program and Mosaiq system of the Varian radiation system (Clinac 2100 C/D) at the Department of Radiotherapy, Institute of Oncology Ljubljana from 1 November 2014 to 31 January 2017. 30 patients with rectal and anal canal cancer, irradiated by intensity-modulated radiotherapy were included in the study. 15 patients were irradiated with a bolus, while the other 15 patients were irradiated without it. The analysis was made using Microsoft Office Excel 2016 and IBM SPSS 24 computer programs. Results and discussion: The results indicated multiple side effects in patients irradiated using a bolus (radiodermatitis - RD, burning pain in perianal and inguinal area, burning or obstructed urination). To determine the differences between the patients treated with and without a bolus, we used the chi-square test. The most pronounced was RD, which most often presents itself in patients treated with a bolus; namely first-degree (53.3 %; p = 0.003), second-degree (86.7 %; p < 0.001 ), and third-degree (46.7 %; p = 0.010). Statistically significant differences were present in the onset of RD, in all degrees, depending on whether the patients were irradiated with or without a bolus. The most pronounced side effects in patients treated without a bolus were diarrhea and dysuria. Conclusion: In the irradiation of surface tumors, a bolus is used so that the target volume receives the optimum dose. It is crucial that the resulting side effects are recognized and treated as soon as they occur.